The effect of compulsory schooling laws on teenage marriage and births in Turkey - Murat G. Kirdar; Meltem Dayıoğlu Tayfur; İsmet Koç (TÜSİAD-Koç University Economic Research Forum, 2010)
This paper estimates the impact of the extension of compulsory schooling in Turkey from 5 to 8 years on the marriage and fertility behavior of teenage women in Turkey using the 2008 Turkish Demographic and Health Survey. We find that the new education policy reduces the probability of marriage and giving birth for teenage women substantially: the probability of marriage by age 16 is reduced by 44 percent and the probability of giving birth by age 17 falls by 36 percent. The effects of the education policy on the time until marriage and firstbirth persist beyond the completion of compulsory schooling. In addition, we find that the delay in the time until first-birth is driven by the delay in the time until marriage. After a woman is married, the rise in compulsory schooling years does not have an effect on the duration until her first-birth. Finally, we find that the education policy was more effective in reducing early marriage than a change in the Civil Code aimed for this purpose.
Keywords: J12; J13; I20; D10; 330; Age at marriage; Fertility; Education; Compulsory Schooling; Ehe; Altersgruppe; Geburtenrate; Familienplanung; Bildungsverhalten; Privater Haushalt; Türkei